2011
DOI: 10.1002/pbc.23308
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for elevated INR values during warfarin therapy in hospitalized pediatric patients

Abstract: Elevated INR values occur often in patients receiving warfarin while admitted to a tertiary care pediatric facility and modifiable risk factors exist for elevated INR values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
(23 reference statements)
1
15
0
Order By: Relevance
“…Administrative claims data were the most common sources of primary ADE detection, used in 37.5 % (15/40) of studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Chart review was used as a primary ADE detection method in 35 % (14/40) of studies [8,[24][25][26][27][28][29][30][31][32][33][34][35][36], and survey or patient/ parent report was used in 27.5 % (11/40) of the studies [27,32,33,[37][38][39][40][41][42][43][44]. Direct documentation by research staff was used by three studies (7.5 %) [45][46][47].…”
Section: Resultsmentioning
confidence: 99%
“…Administrative claims data were the most common sources of primary ADE detection, used in 37.5 % (15/40) of studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Chart review was used as a primary ADE detection method in 35 % (14/40) of studies [8,[24][25][26][27][28][29][30][31][32][33][34][35][36], and survey or patient/ parent report was used in 27.5 % (11/40) of the studies [27,32,33,[37][38][39][40][41][42][43][44]. Direct documentation by research staff was used by three studies (7.5 %) [45][46][47].…”
Section: Resultsmentioning
confidence: 99%
“…Hylek et al found that bleeding risk increased significantly in patients over 80 years who had an INR level over 4 and who had been using warfarin for more than 90 days [9]. Similarly, in a study of 184 warfarin-using patients younger than 12 years, INR levels were higher in those using warfarin for an extended duration [10]. However, Aspinall et al found that the duration of warfarin use was not an independent risk factor for increased bleeding risk in patients followed up in an anticoagulation clinic [11].…”
Section: Discussionmentioning
confidence: 99%
“…In our knowledge, there have been very few reports on this subject. The previous reports are either episodic case reports (presentation in congress) or observations for very short period (<2 weeks) [8]- [14]. This study showed that the use of PPI on top of warfarin did not change anti-coagulation action of warfarin for more than 6 weeks.…”
Section: Discussionmentioning
confidence: 76%
“…However, it is not known how this pharmacological difference among PPI is relevant to the clinical practice. In fact, there are few clinical studies on this matter [11]- [14]. Some studies pointed out that PPI increased the anti-coagulation effect of warfarin [11] [14], i.e., INR was increased, but their observation periods were too short (1 to 2 weeks) to draw a definite conclusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation